Hi there!
Since we have 2 variables in the given equation, and you only want to solve for one, the other will end up in your answer.
![6x + 8y = 12](https://tex.z-dn.net/?f=6x%20%2B%208y%20%3D%2012)
Step 1) Add 8y to both sides.
![6x - 8y + 8y = 12 + 8y 6x = 8y + 12](https://tex.z-dn.net/?f=6x%20-%208y%20%2B%208y%20%3D%2012%20%2B%208y%206x%20%3D%208y%20%2B%2012)
Step 2) Divide both sides by 6.
![\frac{6x}{6} = \frac{8y + 12}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6x%7D%7B6%7D%20%3D%20%20%5Cfrac%7B8y%20%2B%2012%7D%7B6%7D%20)
![x = \frac{4}{3} y + 2](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B4%7D%7B3%7D%20y%20%2B%202)
Final Answer -
![x = \frac{4}{3} y + 2](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B4%7D%7B3%7D%20y%20%2B%202)
Hope this helps! :D
Answer:1.0%
Step-by-step explanation:
hopes it help
Answer:
D) ![(g\cdot f)(x)=x](https://tex.z-dn.net/?f=%28g%5Ccdot%20f%29%28x%29%3Dx)
Step-by-step explanation:
If two functions
and
are inverse of each other, then the following conditions must be true:
i. ![(f\cdot g)(x)=x](https://tex.z-dn.net/?f=%28f%5Ccdot%20g%29%28x%29%3Dx)
ii. ![(g\cdot f)(x)=x](https://tex.z-dn.net/?f=%28g%5Ccdot%20f%29%28x%29%3Dx)
Therefore, out of the four choices available, only option D matches the condition for inverse function to exist.
Therefore, ![(g\cdot f)(x)=x](https://tex.z-dn.net/?f=%28g%5Ccdot%20f%29%28x%29%3Dx)
Answer:
C. 200 minutes, $260
Step-by-step explanation:
The equations would look like this
Lynn = y = 1.10x + 40
Heather = y = 1.15x + 30
Now just plug in.
Lynn
260 = 1.10(200) + 40
260 = 220 + 40
260 = 260
Heather
260 = 1.15(200) + 30
260 = 230 + 30
260 = 260
Hope this helps ya! Keep smiling!
i am not very good it math but i thing is B so yeah bye.